New Perspectives on Graphene/Polymer Fibers and Fabrics for Smart Textiles: The Relevance of the Polymer/Graphene Interphase - Salavagione, Horacio J.; Gómez-Fatou, Marián A.; Shuttleworth, Peter S.; Ellis, Gary J. (Frontiers in Materials, 2018)
The fast-growing interest in smart textiles for wearable electronics or sensors is stimulating considerable activity in the development of functional fibers and fabrics that incorporate graphene, due to its outstanding electrical, mechanical and thermal properties, amongst others. This paper provides an overview of the current state- of-the-art of research in this field, and a perspective on the factors decisive to its growth, in particular the polymer-graphene interphase.